Sources of organochlorine pesticides in air in an urban Mediterranean environment: volatilisation from soil - Lammel, Gerhard; Klánová, Jana; Erić, Ljiljana; Ilić, Predrag; Kohoutek, Jiří; Kovacić, Igor (Journal of environmental monitoring, 2011)
Organochlorine pesticide (OCP) cycling was studied in the area of Banja Luka, Bosnia and Herzegovina, over 3 days in summer with high temporal (4 h-means) and spatial (3 sites distanced 3-6 km) resolutions. Elevated levels of DDX compounds (i.e. o,p'- and p,p'-isomers of DDT, DDE and DDD, 44-74 pg m(-3) at the urban sites and 27 pg m(-3) as a background level), HCH (α-, β- and γ-isomers, 52-70 vs. 147 pg m(-3)), HCB (34-48 vs. <0.1 pg m(-3)) and pentachlorobenzene (6.8-9.9 vs. 6.0 pg m(-3)) were found. The variation of OCP levels at the two urban sites was not in phase, except for most DDX compounds. This was related to background levels, which for HCH were higher than in the urban area. Vertical profiles between samples collected from 1.1 and 2.3 m (part of the time 0.6 and 2.3 m) above a soil, which was only moderately contaminated by OCPs (0.12 ng g(-1) HCH, 0.11 ng g(-1) DDX, 0.44 ng g(-1) HCB) were analysed. Volatilisation from the ground caused negative vertical concentration gradients of HCH isomers (day and night), but not for HCB (except for 1 day-time sample) and DDX compounds (except p,p'-DDD, day-time, sporadically). The concentration in air and the vertical concentration gradient of the HCH isomers varied with air temperature (day-time maxima), while the variation of the HCB concentration was inversely related to air temperature and was determined by mixing (night-time maxima). α- and β-HCH were volatilised from soil throughout the three days, even during periods of cooling. Fugacity calculations, based on the absorption in soil organic matter as the process determining retention in soil, underestimated the volatilisation of β-HCH and p,p'-DDD. It is concluded that the representativeness of point measurements of OCPs in urban areas is limited by the spatial variability of soil contamination.
Keywords: Bosna a Hercegovina; Volatilization; Environmental Monitoring; Hydrocarbons, Chlorinated; látky znečišťující půdu; Bosnia and Herzegovina; Pesticides; látky znečišťující vzduch; Agriculture; monitorování životního prostředí; volatilizace; Cities; Soil Pollutants; pesticidy; zemědělství; chlorované uhlovodíky; velkoměsta; Air Pollutants